Enhancing Arabic Vocabulary Acquisition: Evaluating Rosetta Stone Application for College Students - Arifin, Fitriah Junita; Hikmah, Khizanatul (Indonesian Journal of Islamic Studies, 2024)
This study investigates the effectiveness of utilizing the Rosetta Stone application as a tool for learning Arabic vocabulary, particularly among college students at Rumah Binaan Indonesia Malang. Employing a case study approach involving observation, interviews, and documentation, the research demonstrates that the application facilitates independent learning, offering exercises with immediate feedback. The findings indicate that college students find the Rosetta Stone application user-friendly and flexible, allowing for convenient Arabic vocabulary acquisition at any time and place. This research sheds light on the potential of smartphone applications, such as Rosetta Stone, in supporting language learning endeavors for beginners. Highlight: This study assesses the effectiveness of the Rosetta Stone application as a valuable tool for Arabic vocabulary acquisition, specifically tailored for college students at Rumah Binaan Indonesia Malang. Employing a comprehensive case study methodology, involving observation, interviews, and documentation, the research substantiates the application's capacity to facilitate independent learning with timely feedback. The findings underscore the user-friendly and adaptable nature of the Rosetta Stone application, enabling convenient Arabic vocabulary acquisition irrespective of time or location. This research illuminates the promising role of smartphone applications, like Rosetta Stone, in supporting language learning initiatives, particularly for beginners. Keyword: Rosetta Stone Application, Arabic Vocabulary Learning, College Students, Language Learning Technology, Independent Learning